DOI: 10.7190/shu-thesis-00445
|View full text |Cite
|
Sign up to set email alerts
|

Framework for embedding industry 4.0 in UAE emergency management

Abstract: Disasters, natural and man-made, are on the increase. It is universally accepted that global warning and climate change drive the rate and the severity of natural disasters. Rapid industrialisation, regional conflicts and socio-political tensions are increasing the occurrences of man-made disasters. Emergences created by these disasters need to be handled efficiently and effectively to reduce the impact on affected communities. Emergency Management Cycle with four phases (mitigation-preparedness-response-recov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 70 publications
1
0
0
Order By: Relevance
“…Using the historical dialectical materialism approach, the study found out that weak primary and secondary school curriculum and admission of weak students to technical education programmes was the main course of skills gap in Tanzania. Similar findings in regard to low-quality input among them low entry grades that make it difficult for the training institutions to respond adequately to the industry's needs were established by Alsaaideh (2020) in Jordan, Alshamsi (2020) in United Arab Emirates, Anindo (2016) in Nairobi County Kenya, Barasa and Kwisira (2019) in Kakamenga County Kenya, Bogonko (2018) in Nyamira County Kenya, Koboonye (2020) in in Botswana, Mwila (2016) in Malawi, Ngure (2015) in Kenya, Sakamba in Zambia. These finding emphasize the fact that open admission policy is a challenge to skills development globally hence requiring further investigation.…”
Section: Related Literature Reviewsupporting
confidence: 65%
“…Using the historical dialectical materialism approach, the study found out that weak primary and secondary school curriculum and admission of weak students to technical education programmes was the main course of skills gap in Tanzania. Similar findings in regard to low-quality input among them low entry grades that make it difficult for the training institutions to respond adequately to the industry's needs were established by Alsaaideh (2020) in Jordan, Alshamsi (2020) in United Arab Emirates, Anindo (2016) in Nairobi County Kenya, Barasa and Kwisira (2019) in Kakamenga County Kenya, Bogonko (2018) in Nyamira County Kenya, Koboonye (2020) in in Botswana, Mwila (2016) in Malawi, Ngure (2015) in Kenya, Sakamba in Zambia. These finding emphasize the fact that open admission policy is a challenge to skills development globally hence requiring further investigation.…”
Section: Related Literature Reviewsupporting
confidence: 65%